Results and evaluation of a first‐in‐human study of RG7342, an mGlu5 positive allosteric modulator, utilizing Bayesian adaptive methods. (18th December 2017) - Sturm, Stefan; Delporte, Marie‐Laure; Hadi, Salah; Schobel, Scott; Lindemann, Lothar; Weikert, Robert; Jaeschke, Georg; Derks, Michael; Palermo, Giuseppe
Abstract : Aim: The objectives of this first‐in‐human study were to evaluate the safety and tolerability, pharmacokinetics and pharmacodynamics, and maximum tolerated dose (MTD) of single ascending oral doses of RG7342, a positive allosteric modulator (PAM) of the metabotropic glutamate receptor 5 (mGlu5) for the treatment of schizophrenia, in healthy male subjects. Methods: This was a single‐centre, randomized, double‐blind, adaptive study of 37 subjects receiving single ascending oral doses of RG7342 (ranging from 0.06–1.2 mg, n = 27) or placebo ( n = 10). A modified continual reassessment method, with control for the probability of overdosing based on the occurrence of dose‐limiting events (DLEs), was applied to inform the subsequent dose decisions for RG7342. Results: DLEs consisted of dizziness, nausea and vomiting, and the incidence and severity of these adverse events increased in a concentration‐dependent manner. RG7342 doses of 1.2 mg under fasting conditions, which reached a mean maximum plasma concentration (Cmax ) of 10.2 ng ml –1, were not tolerated (four out of six subjects experienced DLEs). RG7342 showed dose‐proportional pharmacokinetics, with rapid absorption and a biphasic decline, and a mean terminal half‐life estimated to be >1000 h. Conclusions: Single oral doses of RG7342 were generally tolerated up to 0.6 mg under fasting and 0.9 mg under fed conditions in healthy subjects. Bayesian adaptive methods describing the probability of DLEs were applied effectively to support dose escalation. MTDs (fasting, fed) were associated with a Cmax of 6.5 ng ml –1 . The development of RG7342 was discontinued owing to the potential challenges associated with a long half‐life in context of the observed adverse events.